Informação estratégica para o trabalho: uma proposta de suporte informacional para a empregabilidade - Bastos Junior, Luis Claudio dos Santos (2019)
This research aims to develop a proposal of informational support for employability through the Information Observatory of Labor (ILO) in favor of Sergipe professionals. This action is justified by the situation of the unemployed in the state, and the lack of research related to the subject. The specific objectives are: To identify the profile of the organizations belonging to the framework of the Commercial and Business Association of Sergipe (ACESE); Raise the main professional skills demanded by the organizations that make up the Commercial and Business Association of Sergipe (ACESE); To characterize professional skills in the service, product, industry and third sectors of the Commercial Association of Sergipe (ACESE); To make available through tables the competencies raised in the research, contributing informationally with the Information Observatory of Labor (ILO). Regarding the methodology, this study is classified as descriptive, with a survey strategy and a qualitative-quantitative approach. The data were collected through the application of semistructured questionnaires with the owners of companies associated to ACESE, and later, an interview of deepening the theme with the entrepreneurs selected from each sector listed. It was concluded with the research that the educational formation is fundamental for hiring in the research companies, mainly in front of the new Technologies of Information and Communication (TICs), in addition, it was evidenced the relevance that the competences linked to the behavior have for like the contracting of the professionals for these Sergipe companies. This time, the study developed tables with the information collected on employability, aiming to guide these professionals in employability.